2021
DOI: 10.1039/d1cc03742k
|View full text |Cite
|
Sign up to set email alerts
|

Design of phase-transition molecular solar thermal energy storage compounds: compact molecules with high energy densities

Abstract: Compact azobenzene derivatives with various functional groups are investigated to realize total photon and thermal energy storage over 300 J g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…80 Later on, using a series of further optimized phase-change AZO systems a maximum energy storage density up to 0.3 MJ kg À1 was achieved, showing that the molecular size and polarity can also significantly affect the energy storage capacity. 81 Recently, arylazopyrazole-based photoswitches were reported to undergo efficient PCLT with nearly complete photoconversion ($97%) at room ll OPEN ACCESS temperature. 62 High energy densities of 0.32-0.37 MJ kg À1 were achieved after combining 0.16-0.19 MJ kg À1 of photochemical energy and 0.14-0.21 MJ kg À1 of latent heat stored during E/Z isomerization and crystal melting, respectively.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…80 Later on, using a series of further optimized phase-change AZO systems a maximum energy storage density up to 0.3 MJ kg À1 was achieved, showing that the molecular size and polarity can also significantly affect the energy storage capacity. 81 Recently, arylazopyrazole-based photoswitches were reported to undergo efficient PCLT with nearly complete photoconversion ($97%) at room ll OPEN ACCESS temperature. 62 High energy densities of 0.32-0.37 MJ kg À1 were achieved after combining 0.16-0.19 MJ kg À1 of photochemical energy and 0.14-0.21 MJ kg À1 of latent heat stored during E/Z isomerization and crystal melting, respectively.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Furthermore, Xu et al reported a novel photochromic dendrimer obtained by grafting Azo units onto dendrimers, which exhibited excellent solar energy storage, controlled heat release, self-repair and controllable adhesive switching properties [22,23] . Moreover, the research group of Han successfully designed new photoliquefiable Azo molecules featuring photocontrolled latent heat storage [24] . Therefore, Azo photoswitches with PCLT capacities have been investigated as promising energy harvest and storage materials.…”
Section: Introductionmentioning
confidence: 99%
“…The isomerization is sometimes accompanied by a solid-liquid transition, 25,26 and the transition energy can be stored by light irradiation. [27][28][29][30] The combination of cold crystallization and photoisomerization is a promising method for nding new functional energy storage systems.…”
Section: Introductionmentioning
confidence: 99%